Comparative Analysis of Pesticide Use Determinants Among Smallholder Farmers From Costa Rica and Uganda. (December 2020) - Staudacher, Philipp; Fuhrimann, Samuel; Farnham, Andrea; Mora, Ana M; Atuhaire, Aggrey; Niwagaba, Charles; Stamm, Christian; Eggen, Rik IL; Winkler, Mirko S
Pesticides are used globally in agriculture and pose a threat to the health of farmers, communities, and the environment. Smallholder farmers in low- and middle-income countries have generally a low socio-economic status and educational level. Consequently, they are particularly vulnerable to negative impacts of pesticides on their health, yields, or land. In a Knowledge, Attitude, and Practices study, we compared the pest management practices between a market-oriented farming system in Zarcero County, Costa Rica, and a subsistence-based farming system in Wakiso District, Uganda. We conducted a cross-sectional survey among smallholder farmers from Costa Rica (n = 300) in 2016 and from Uganda (n = 302) in 2017. We enrolled conventional and organic farmers, but also farmers with mixed practices and non-applicators of any pest management strategy. We found that the majority of pesticides used in both case studies are classified as highly hazardous by the World Health Organization. While more than 90% of smallholder farmers from both countries were aware of the negative health effects of pesticide exposure, <11% in Costa Rica and <2% in Uganda reported using personal protective equipment every time they handled or applied pesticides. Hygiene and other safe use practices were not adopted by all farmers (<61%), especially among farmers applying more hazardous pesticides. Conventional farmers from Costa Rica (14%) and Uganda (19%) reported disposing pesticide residuals into rivers. Using a logistic regression we found that organic farmers were more likely to having been trained on safe pesticide use practices. Using a robust regression, we observed that smallholder household income was primarily driven by education and not directly by the use of synthetic pesticides. Our results suggest that negative effects of pesticides can be managed over the whole life cycle, from purchase, via storage and application to residual and waste management by fostering professionalization of farmers. We advise future safe use and handling interventions to consider the pesticide use-related socioeconomic and demographic findings highlighted in this paper.